Occupational health and safety in a hazardous waste disposal facility using Industry 4.0 technologies: A Fine Kinney risk analysis - Demir, Yasemin; Ersöz, Melike; Özcan, H. Kurtuluş; Demir, Göksel (Frontiers in Life Sciences and Related Technologies, 2024)
Considering the environmental and human health impacts of rapidly growing industries and the uncontrolled increase in the amount of waste they generate; hazardous waste disposal facilities play a critical role in protecting public health. Hazardous waste disposal facilities include various multidisciplinary systems such as landfills, biogas plants, laboratories, medical waste landfills, wastewater plants, and incineration plants. This study aims to examine each facility in a sample hazardous waste disposal facility in terms of occupational health and safety to identify risks, and to offer recommendations for solutions. The sample facility was visited, and each section was examined separately, and preliminary information was obtained using a checklist. In light of the preliminary information obtained, risk analysis was performed and the results were presented with recommendations. Fine Kinney Risk Assessment method was preferred because it is more comprehensive than other risk analysis methods based on probability and severity and can adapt to multiple disciplines. In addition, it is stated that automated processes within the scope of Industry 4.0 can have a positive impact on the prevention of occupational accidents by leading to a reduction in human work and thus a reduction in worker-waste contact. As a result of the risk assessment, 68 risks were identified in the facilities visited, most of which were substantial.